2‐ and 2, 7‐Substituted para‐N‐Methylpyridinium Pyrenes: Syntheses, Molecular and Electronic Structures, Photophysical, Electrochemical, and Spectroelectrochemical Properties and Binding to Double‐Stranded (ds) DNA. Issue 8 (7th January 2021) - Kole, Goutam Kumar; Merz, Julia; Amar, Anissa; Fontaine, Bruno; Boucekkine, Abdou; Nitsch, Jörn; Lorenzen, Sabine; Friedrich, Alexandra; Krummenacher, Ivo; Košćak, Marta; Braunschweig, Holger; Piantanida, Ivo; et al.
Abstract: Two N ‐methylpyridinium compounds and analogous N ‐protonated salts of 2‐ and 2, 7‐substituted 4‐pyridyl‐pyrene compounds were synthesised and their crystal structures, photophysical properties both in solution and in the solid state, electrochemical and spectroelectrochemical properties were studied. Upon methylation or protonation, the emission maxima are significantly bathochromically shifted compared to the neutral compounds, although the absorption maxima remain almost unchanged. As a result, the cationic compounds show very large apparent Stokes shifts of up to 7200 cm −1 . The N ‐methylpyridinium compounds have a single reduction at ca. −1.5 V vs. Fc/Fc + in MeCN. While the reduction process was reversible for the 2, 7‐disubstituted compound, it was irreversible for the mono‐substituted one. Experimental findings are complemented by DFT and TD‐DFT calculations. Furthermore, the N ‐methylpyridinium compounds show strong interactions with calf thymus (ct)‐DNA, presumably by intercalation, which paves the way for further applications of these multi‐functional compounds as potential DNA‐bioactive agents. Abstract : Multi‐functional pyrene‐viologens : The synthesis, molecular and electronic structures, photophysical, electrochemical, and spectroelectrochemical properties of 2‐ and 2, 7‐substituted para ‐ N ‐methylpyridinium pyrene compounds are described along with detailed theoretical calculations. These compounds show strong interactions with calf thymus (ct)‐DNA, presumably by intercalation.